Dibenzothiophenesulfilimines: a convenient approach to intermolecular rhodium-catalysed C−H amidation - Antoni, Patrick W.; Mackenroth, Alexandra; Mulks, Florian; Rudolph, Matthias; Helmchen, Günter; Hashmi, A. Stephen K. (Chemistry - a European journal, 2020)
A sulfilimine‐based Group 9 transition‐metal‐catalysed C−H amidation procedure is reported. Dibenzothiophene‐based sulfilimines were shown to constitute a class of novel amidation reagents which enable the transfer of a wide range of N‐sulfonyl and N‐acyl moieties. It was demonstrated that sulfilimines, which are easily accessible from cheap reagents, are safe‐to‐handle and represent broadly applicable amidation reagents. The dibenzothiophene can be recycled after use. The C−H amidation was shown to proceed with high selectivity and gave the mono‐amidated products, mostly in good to excellent yields.
Gesehen am 02.09.2020